Identification of Barriers to Self-Care Behaviors in Patients with Cerebral Palsy - Leila Farhoumandfar; Anahita Khodabakhshi-koolaee; Mohammad Reza Falsafinejad (Zanjan University of Medical Sciences and Health Services, 2021)
Background: There are many barriers to self-care behaviors in adult patients with cerebral palsy (CP) that can cause various problems in their daily life and social activities. Barriers to self-care behaviors affect various aspects of adult CP patients' lives, causing physical, psychological, and social problems. Objectives: The present study aimed to identify the barriers to self-care behaviors in CP patients. Methods: This study was conducted using a qualitative method based on the grounded theory. The participants were selected through purposive sampling among the clients of the Cerebral Palsy Supporters House and Raad Charity Educational Center in Tehran, Iran, in 2020. The participants included six men and nine women with CP, aged 20 to 40 years. The data were collected via semi-structured interviews. After interviewing 15 participants, we reached theoretical data saturation. The interviews were recorded and then transcribed. Data based on Corbin and Strauss's theory (2008) were analyzed using open, axial, and selective coding. Results: The barriers to self-care behaviors were conceptualized into 39 open codes and seven categories using axial coding. The categories were as follows: "Psychological barriers to perceiving the importance of self-care behaviors", "physical and motor disabilities", "dissatisfaction with body shape and appearance", "excessive family concerns and support", "employment limitations", "negative and judgmental views of the society", and "economic and financial concerns and uncertainties about the future". Conclusion: The results showed that barriers to self-care behaviors in CP patients affect their well-being and quality of life. The results of the present study can contribute to our understanding of the barriers to self-care behaviors and help us develop interventions and strategies to educate CP patients and their families.